(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to investigate the effect of using the intructional computer individually or through the cooperative groups on the achievement of the ninth grade students in mathematics compared to the traditional method. The experimental method adapted three groups out of three schools were chosen, two groups of the students where applied the computer method. The comtrol group used the simple random method, and it used the diagnostic test as tool for the study.The result showed that there is a statistically significant difference between the mean scores of the experimental groups and the control group on the post-test for the two experimental groups.